2019
DOI: 10.3390/pr7100770
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies and Moisture Diffusivity During Cocoa Bean Roasting

Abstract: Cocoa bean roasting allows for reactions to occur between the characteristic aroma and taste precursors that are involved in the sensory perception of chocolate and cocoa by-products. This work evaluates the moisture kinetics of cocoa beans during the roasting process by applying empirical and semi-empirical exponential models. Four roasting temperatures (100, 140, 180, and 220 °C) were used in a cylindrically designed toaster. Three reaction kinetics were tested (pseudo zero order, pseudo first order, and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…There are some gaps indicating tissue-free areas in these parts of the beans. Moisture diffusion and shrinkage effects inside the bean during the fermentation/drying process as possible causation have already been described by others in the literature. , Overall, the elemental maps obtained by means of μXRF are in good agreement with the data from the LA-ICP-MS approach . In the roasted bean, the embryonic region is not in the sectional plane; somewhat more faintly delineated are the structures of the cotyledon interfaces noticeable from the S, K, and Ca fluorescence intensity distributions.…”
Section: Resultssupporting
confidence: 81%
“…There are some gaps indicating tissue-free areas in these parts of the beans. Moisture diffusion and shrinkage effects inside the bean during the fermentation/drying process as possible causation have already been described by others in the literature. , Overall, the elemental maps obtained by means of μXRF are in good agreement with the data from the LA-ICP-MS approach . In the roasted bean, the embryonic region is not in the sectional plane; somewhat more faintly delineated are the structures of the cotyledon interfaces noticeable from the S, K, and Ca fluorescence intensity distributions.…”
Section: Resultssupporting
confidence: 81%
“…The value reported for willow stems match with the typical diffusion coefficients for humidity transport in wood, i.e., 1-5 × 10 −10 m 2 /s as reported by Baronas et al [47]. Studying dehydration kinetics of fermented cocoa beans, Adrover and Brasiello [48] found typical diffusion coefficients of 7.5 × 10 −11 m 2 /s at 25 • C. Domínguez-Pérez et al [49] found for roasted cocoa beans moisture diffusion coefficients in the range 1.26-5.70 × 10 −10 m 2 /s. For lemongrass, Nguyen et al [50] found effective diffusion coefficient in the range from 7.64 × 10 −11 to 1.48 × 10 −10 m 2 /s.…”
Section: Introductionsupporting
confidence: 83%
“…Several studies have investigated the kinetics of cocoa roasting processes in terms of water loss. Domínguez-Pérez et al (2019) found that the water loss was represented with a pseudofirst-order equation, and used the Arrhenius equation to find the temperature dependence. Hii, Menon, Chiang, and Sharif (2017) observed the typical exponential decay of cocoa's moisture content and reported the moisture diffusivities as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%